2005
DOI: 10.1124/jpet.105.087981
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation-Mediated Hypoxia and Neutrophil-Dependent Hepatic Injury in Rats Given Lipopolysaccharide and Ranitidine

Abstract: Idiosyncrasy-like liver injury occurs in rats cotreated with nonhepatotoxic doses of ranitidine (RAN) and bacterial lipopolysaccharide (LPS). Hepatocellular oncotic necrosis is accompanied by neutrophil (PMN) accumulation and fibrin deposition in LPS/RAN-treated rats, but the contribution of PMNs to injury has not been shown. We tested the hypothesis that PMNs are critical mediators of LPS/RAN-induced liver injury and explored the potential for interaction between PMNs and hemostasisinduced hypoxia. Rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 37 publications
6
57
0
Order By: Relevance
“…Hepatic inflammatory infiltrates in LPS/RAN-treated rats comprised predominantly PMNs, suggesting the possibility of a role for these cells in the liver injury (Luyendyk et al, 2005). In addition, the expression of several genes involved in hemostasis or the response to …”
Section: Ranitidine-induced Idiosyncratic Hepatotoxicity Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic inflammatory infiltrates in LPS/RAN-treated rats comprised predominantly PMNs, suggesting the possibility of a role for these cells in the liver injury (Luyendyk et al, 2005). In addition, the expression of several genes involved in hemostasis or the response to …”
Section: Ranitidine-induced Idiosyncratic Hepatotoxicity Inmentioning
confidence: 99%
“…Cotreatment with either anticoagulant heparin, the fibrinolytic agent streptokinase, or a PAI-1 inhibitor decreased the hepatocellular injury induced by LPS/RAN, suggesting a role for the hemostatic system . Hepatic hypoxia occurred in LPS/RAN-treated rats, and heparin reduced the tissue hypoxia and fibrin deposition (Luyendyk et al, 2005). RAN seems to selectively augment coagulation and PAI-1 production triggered by LPS, and this in turn causes fibrin deposition that leads to tissue hypoxia and hepatocyte death.…”
Section: Involvement Of Hemostasis Neutrophils and Tumor Necrosis Fmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Toxicity was accompanied by a marked neutrophil infi ltration and inhibited by depletion of neutrophils with antineutrophil antibodies. 38 Toxicity was also associated with fi brin deposition and inhibited by heparin. This data suggest that LPS-potentiated toxicity involves a combination of fi brin deposit-induced hypoxia and neutrophil-mediated cell damage.…”
Section: Lipopolysaccaride-potentiated Hepatotoxicitymentioning
confidence: 98%
“…This data suggest that LPS-potentiated toxicity involves a combination of fi brin deposit-induced hypoxia and neutrophil-mediated cell damage. 38 It was suggested that this could be a dominant mechanism for hepatic DHRs, and that random exposure to LPS or other infl ammatory condition could explain the time course of DHRs. 39 Although neutrophils can be part of the cellular infi ltrate in hepatic DHRs, the dominant cells are usually mononuclear.…”
Section: Lipopolysaccaride-potentiated Hepatotoxicitymentioning
confidence: 99%